2020
DOI: 10.3390/metabo10030087
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Shifts Induced by Marathon Race Competition Differ between Athletes Based on Level of Fitness and Performance: A Substudy of the Enzy-MagIC Study

Abstract: This study compared metabolite shifts induced by training for, participation in, and recovery from a marathon race competition among athletes divided into three groups based on fitness (relative maximum oxygen uptake (VO2max)) and performance levels (net running time). Plasma samples from 76 male runners participating in the Munich Marathon were analyzed for metabolite shifts using a targeted metabolomics panel. For the entire cohort of runners, pronounced increases were measured immediately after the race for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
(54 reference statements)
4
21
0
Order By: Relevance
“…The data from this study overall showed enhanced FA and BCAA utilization capacities in high- versus low-performance rats. While the increased FA oxidation capacities in high-performance rats are in line with findings from human marathon runners [ 73 ] described above, the amino acid results between these studies seem contradictory. However, the absence of significant changes in both plasma and muscle amino acids in low-performance rats may be due to the relatively short exercise bout (10 min) that may have been insufficient to induce protein breakdown as opposed to the 45-min run in high-performance rats.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regusupporting
confidence: 58%
See 3 more Smart Citations
“…The data from this study overall showed enhanced FA and BCAA utilization capacities in high- versus low-performance rats. While the increased FA oxidation capacities in high-performance rats are in line with findings from human marathon runners [ 73 ] described above, the amino acid results between these studies seem contradictory. However, the absence of significant changes in both plasma and muscle amino acids in low-performance rats may be due to the relatively short exercise bout (10 min) that may have been insufficient to induce protein breakdown as opposed to the 45-min run in high-performance rats.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regusupporting
confidence: 58%
“…Metabolomic responses to exercise in blood have also been shown to be influenced by an individual’s level of fitness. For instance, in a study by Schader and colleagues [ 73 ], male amateur marathon runners were divided into top ( n = 18), average ( n = 40) and low ( n = 18) performers, based on VO 2 max (~63, 50 and 42 mL × min −1 × kg −1 , respectively) and race completion time (~175, 225 and 277 min, respectively). Blood samples from these three groups were examined for potential differences in metabolomic responses to marathon running.…”
Section: Metabolomic and Lipidomic Analyses Of Acute Exercise-regumentioning
confidence: 99%
See 2 more Smart Citations
“…4.4 | Endurance athletes have higher lysoPC a C18:1 and C18:2 concentrations, which may be linked to cardiovascular fitness Endurance athletes had higher concentration of lysoPC a C18:1 than bodybuilders and controls. Earlier studies have already associated lysoPCs containing 18 carbons with endurance traits (Felder et al, 2017;Schader et al, 2020). Specifically, lysoPC a C18:1 was, among other lysoPCs, reported to increase after several weeks of endurance training (Felder et al, 2017).…”
Section: Endurance Athletes Have Higher Cpt1ratio Suggesting Higher Fat Oxidationmentioning
confidence: 91%